Effectiveness of Nigerian Bamboo Activated with Different Activating Agents on the Adsorption of BTX - FT Ademiluyi; O Braide (Journal of Applied Sciences and Environmental Management)
The effectiveness of Nigerian Bamboo activated with different activating agents on the adsorption of BTX was investigated. A series of activated carbons was prepared from Nigerian bamboo, carbonized at 400oC – 500oC and impregnated with different concentrations of four acids at 800oC in a muffle furnace for 2 hours. The resultant products were further adsorbed into BTX in aqueous and vapour phases. The best activating agent for adsorption of BTX vapour was 0.143M trioxonitrate (v) acid, while the best activating agent for adsorption of BTX in aqueous solution was hydrochloric and trioxonitrate (v) acid. Adsorption of BTX was found to be more of chemisorptions than ordinary physical adsorption. The differences in the adsorption of the three bamboo type was not affected by the physical geometry of the bamboo but by the chemical composition of the bamboo and type of activating agent used. The activated carbon from bamboo with the best concentration was also found to adsorb BTX favourably and better than a commercial activated carbon with same particle size.